The Use of Birth Plan to Support Waterbirth: A Qualitative Approach - Joyce da Costa Silveira de Camargo; Nádia Zanon Narchi; Kelly Cristina Máxima Pereira Venâncio; Fernanda Marçal Ferreira; Cindy Ferreira Lima; Manuela Néné; Maria Catarina LR Grande (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
Background: The professional resistance to childbirth in water and the limitation of robust scientific evidence to support its safety constitute a context prone to the restriction of women's freedom of choice. The elaboration of the birth plan by pregnant women who wish to experience a birth immersed in water can be an important instrument for the exercise of their choice and autonomy. This qualitative and descriptive case study aim to realize how women experienced their birth plan in two hospitals in Portugal. Results: Face-to-face and videoconferencing interviews were conducted with sixteen women witch speeches were recorded, transcribed, and submitted to content analysis, with the support of NVivo software. The mainly characteristics of the participants were: 76% had a higher level of schooling; 66% lived in a stable union with a partner; 66,7% were nulliparous; 100% were informed and prepared during prenatal sessions about waterbirth and made their birth plan with those sessions; 100% were at term gestation at the time of birth; 100% were referred for immersion in hot water during labour; after birth, all the newborns had Aqua Apgar index between 9 and 10 in the first minute and 10 in the fifth minute. The qualitative analysis allowed to identification of three thematic categories: Legitimising women's choices; Professional resistance and the devaluation of the birth plan: triggers of violence; and, Complete birth plan success. Conclusion: The data showed that birth plan represented a legitimator of women´s choices for experiencing waterbirth, although some of them perceived disregard and disrespect of the plan by health professionals, especially in a context of technocratic model of care. It was found that the birth plan represented a transcendence of the experience of labour and birth, enabling women to experience their choices with fullness, freedom, and specially respect.